Clinical Efficacy of Mind-Regulating Acupuncture on Post-Stroke Depression Based on the “Microbiota-Gut-Brain Axis” Theory: A Randomized Controlled Study - Xie J; Li J; Sun Q; Jiang J (Neuropsychiatric Disease and Treatment)
Jingjun Xie,1 Jinxia Li,2 Qi Sun,1 Jie Jiang1 1Department of Acupuncture, The First People’s Hospital of Huzhou, Huzhou, Zhejiang Province, People’s Republic of China; 2Department of Acupuncture, Huzhou Hospital of Traditional Chinese Medicine, Affiliated to Zhejiang Chinese Medical University, Huzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Jie Jiang, Department of Acupuncture, The First People’s Hospital of Huzhou, No. 158, Guang Chang Hou Road, Huzhou, Zhejiang Province, 313000, People’s Republic of China, Email jairjiang@163.comObjective: This study explored the clinical efficacy and mechanisms of Mind-Regulating Acupuncture (MRA) for post-stroke depression (PSD) based on the “microbiota-gut-brain axis” theory.Methods: 92 PSD patients were randomly divided into an observation group (received conventional therapy + MRA) and a control group (conventional therapy only). After 8 weeks of treatment, multiple indicators including depression scores, neurological function scores, and levels of neurotransmitters and gut microbiota were compared.Results: MRA significantly improved depressive symptoms, neurological function, and daily living abilities in PSD patients. It increased serum 5-HT and BDNF levels, and regulated gut microbiota, promoting beneficial bacteria and reducing harmful ones.Conclusion: MRA effectively treats PSD, and its mechanism may involve regulating the “microbiota-gut-brain axis”, increasing beneficial gut bacteria, and enhancing 5-HT and BDNF levels.Keywords: post-stroke depression, mind-regulating acupuncture, microbiota-gut-brain axis, gut microbiota